Some considerations on Meconial Amniotic Fluid in the new born babies - Cleopatra Cabrera Cuellar; Nilda B. Cortizo Martínez; Arturo Pérez de Villa; Alina L. Díaz Dueñaz; Sergio Elías Molina Lamothe (Medisur)
Background: Many functions are attributed to amniotic liquid, there is no doubt, after all, about the negative consequences of its alteration. The differentiation between physiological meconium and pathological meconium can modify the perinatal results. Objectives: to determine if the presence of the meconium considered pathological, is significantly related to the morbimortality of the patients. Method: an analytic and prospective study was made, control case type, of 504 newborn children with meconial amniotic liquid, and the same number of newborn children with clear amniotic liquid. Results: the pathological meconial amniotic liquid was associated to a low Apgar percentage, in the first minute of 5,2 %. When the meconial amniotic liquid resulted physiological it was of 0,4 %. The morbility associated to perinatal hypoxia raised from 0,4 % when the meconial amniotic liquid was physiological, and to 4,85 when it was pathological. The necessity of ventilation, associated to the pathological meconial amniotic liquid, was of 3,1 %. There were 3 deaths in the pathological meconial amniotic liquid group, for a 1,3 % of mortality. When the meconial amniotic liquid colour was intensified during delivery labour, it was observed a low Apgar percentage of 11 %. Conclusions: the meconial amniotic fluid is presented in the 23% of the patients in our study increasing its incidence as long as the gestational age and the weight of the patient were higher. Preeclampsia is associated in a very significant way to the presence of meconium which is considered pathological.